A redução da maioridade penal: uma relação dialética entre o garantismo penal e a teoria do direito penal do inimigo no ordenamento jurídico brasileiro - Sousa, Daniel Aquino de (2018)
The current study uses the proposals that aim to reduce the penal age as a base for further analysis of criminal law theories that influences the criminal policies currently adopted by the brazilian legal system. It starts with the premise that brazilian constitutionalism adopts within it the bases of a guarantism theory, as outlined by Luigi Ferrajoli, where the very existence of the criminal law is justified by the need for general prevention within a guarantor and minimum model. Then, based on the fact that criminal laws and regulations are increasingly rigid and emergency, considered the only means of combating the crime rates constant growth, the research turns itself to study the Law and Order moviments, emphasizing the tendencies of criminal policies based on social exclusion as a characteristic of the developed liberal societies, under the pretext of maintaining order, especially the proposals of Ralf Dahrendorf, without neglecting the criticisms of David Garland, Jock Young and Douglas Husak. It is from this observation that the reflections on the insertion of an Enemy Criminal Law practices within the Brazilian criminal system emerges, as diagnosed in one of Gunther Jakobs phases. Finally, it is tried to understand if the Amendment Proposals to the Constitution that aim to reduce the penal age follow a stigmatizing and discriminatory tendency, based on analyzes of comparative law, statistical data, norms inside the Child and Adolescent Statute, the custodial sentence purpose and a Symbolic Criminal Law